Challenges and opportunities for a South America waterway system - Julian David Hunt and Yadu Pokhrel and Suyog Chaudhari and André Luiz Amarante Mesquita and Andreas Nascimento and Walter Leal Filho and Marcel Fortuna Biato and Paulo Smith Schneider and Maurício Antônio Lopes (Cleaner Engineering and Technology, 2022)
South America has been developed from its coast to its hinterlands since the beginning of its Western colonization. However, to this point, no significant effort has been made to integrate its interior. Waterways transportation can be considered the most sustainable inland mode of transportation due to its low CO2 emissions per ton of cargo transport. With this in mind, this paper investigates the history, challenges and opportunities of the past proposals for the construction of the South America Waterway System (SAWS) connecting the La Plata, Amazon, and Orinoco river basins. It focuses on particular challenges of the proposed waterway. (i) a comparison between the deforestation surrounding existing road and waterway infrastructure in the Amazon, (ii) the large water level variation in the Amazon basin, (iii) and the alternatives for storing water to reduce the impacts of floods and droughts in the proposed waterway. We conclude that deforestation surrounding existing waterways is practically zero and that groundwater storage has an important role in storing water for the basin and reservoirs, a limited one. The SAWS can significantly foster South American integration, encourage sustainable extraction of natural resources in the region and help the conservation of the Amazon forest.
Keywords: Governance; Inland waterway; Sustainable development; Water management